Contextualizing Instructional Technology to the Demands of Nursing Education. Issue 1 (January 2020) - Smart, Denise; Ross, Kyle; Carollo, Sandy; Williams-Gilbert, Wendy
Abstract : This article reviews current technologies in nursing education and the impact of technology on learning. The integration of technology into nursing curricula is thought to improve efficiency and enhance student experiences through active learning and interactive learning designs. The following focused questions are explored: (1) What are the current technologies used by university students and faculty in nursing programs? (2) How does that technology influence student learning? The primary themes were student-centered technology, with five subthemes, and faculty-centered technology. Consumers of healthcare (patients) demand quality care and expect highly skilled, compassionate, ethical practitioners; to this end, training and education of future nurses by skilled, qualified nurse educators who are comfortable with technological demands of all aspects of healthcare are fundamental. While it is essential that nurses and nurse educators continue to publish as a mechanism for open discussion and transparency in our teaching and learning approaches, we need higher levels of evidence to strengthen the argument that technology improves the learning environment and student outcomes and has a positive impact on clinical settings and patient care.